Ten-Year Molecular Surveillance of Drug-Resistant Plasmodium spp. Isolated From the China–Myanmar Border - Tang, Tongke; Xu, Yanchun; Cao, Long; Tian, Penghai; Shao, Jiang; Deng, Yan; Zhou, Hongning; Xiao, Bo (Frontiers in Cellular and Infection Microbiology, 2021)
Antimalarial drug resistance has emerged as a major threat to global malaria control efforts, particularly in the Greater Mekong Subregion (GMS). In this study, we analyzed the polymorphism and prevalence of molecular markers associated with resistance to first-line antimalarial drugs, such as artemisinin, chloroquine, and pyrimethamine, using blood samples collected from malaria patients in the China-Myanmar border region of the GMS from 2008 to 2017, including 225 cases of Plasmodium falciparum and 194 cases of Plasmodium vivax. In artemisinin resistance, only the C580Y mutation with low frequency was detected in pfk13, and no highly frequent stable mutation was found in pvk12. In chloroquine resistance, the frequency of K76T mutation in pfcrt was always high, and the frequency of double mutations in pvmdr1 of P. vivax has been steadily increasing every year. In pyrimidine resistance, pfdhfr and pvdhfr had relatively more complex mutant types associated with drug resistance sites, and the overall mutation rate was still high. Therefore, artemisinin-based combination therapies are still suitable for use as the first choice of antimalarial strategy in the China-Myanmar border region in the future.